Efficient Electrosynthesis of Thiazolidin‐2‐imines via Oxysulfurization of Thiourea‐Tethered Terminal Alkenes Using the Flow Microreactor. Issue 6 (12th December 2018) - Islam, Muhammad; Kariuki, Benson M.; Shafiq, Zahid; Wirth, Thomas; Ahmed, Nisar
Abstract : Sulfur‐containing scaffolds play a significant role in many important biological processes. The thiazole‐2‐imine derivatives have gained significant biological attention due to their interesting pharmacological activities and act as potential therapeutic agents. Many of their syntheses suffer from the drawbacks such as the handling of toxic reagents, harsh reaction conditions, longer reaction times and tedious separation procedures. To their easy access, we applied first time flow electrochemical approach under free supporting electrolytes conditions and without the use of expensive catalysts and reagents. This is not only the first electrochemical cyclization to access thiazolidin‐2‐imines also represents the first intramolecular sulfurization of unfunctionalized terminal alkenes. This flow electrolysis of N ‐allylic thioureas generates radical intermediates of nitrogen and sulfur that cyclized via oxysulfurization of terminal alkenes and gives thiazolidin‐2‐imines with good to high yields under mild, green and environmentally friendly conditions. Abstract : The flow electro‐microreactor technology has been applied to synthesize biologically important thiazolidin‐2‐imines in high yields via oxysulfurization of terminal alkenes, only using electricity to generate radical reaction intermediates without applying metal catalysis in solution. A broad range of substrates can be cyclized under mild and environmentally friendly conditions without additional electrolyte.